2020
DOI: 10.1186/s13018-020-01731-5
|View full text |Cite
|
Sign up to set email alerts
|

Does gender influence the outcomes of total ankle arthroplasty in patients with ankle osteoarthritis?

Abstract: Background: Total ankle arthroplasty has progressed as a treatment option for patients with ankle osteoarthritis. However, no studies have been conducted to evaluate the effect of gender on the outcome. The purpose of the present study was to evaluate outcomes, survivorship, and complications rates of total ankle arthroplasty, according to gender differences. Methods: This study included 187 patients (195 ankles) that underwent mobile-bearing HINTEGRA prosthesis at a mean follow-up of 7.5 years (range, 4 to 14… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Lee et al reported that women showed higher prevalence of TAR osteolysis and its associated complications compared with men, but this was not statistically significant. 21 Similarly, we found no significant differences in failure rates and implant survivorship between the 2 groups. 21…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 47%
See 4 more Smart Citations
“…Lee et al reported that women showed higher prevalence of TAR osteolysis and its associated complications compared with men, but this was not statistically significant. 21 Similarly, we found no significant differences in failure rates and implant survivorship between the 2 groups. 21…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 47%
“…21 Similarly, we found no significant differences in failure rates and implant survivorship between the 2 groups. 21…”
Section: Gender Differences In Tar Outcomesmentioning
confidence: 47%
See 3 more Smart Citations